Gaston Bachelard’s theory of epistemological obstacles - Gurgul, Paulina (Hybris, 2016)
Gaston Bachelard discuss the problem of the rationality of scientific thinking in terms of epistemological obstacles. In book The Formation of the Scientific Mind philosopher characterizes scientific attitude as an attempt to eliminate the impact of affective images on thinking, which is possible in the process of psychoanalysis of objective knowledge. Bachelard indicates positive model for science: an abstract thought, constructing their own research subjects. Only a constantly renewed cognitive effort can become a source of new ideas.